A study of predictive and prognostic histopathologic factors in breast conservation therapy - Dr. Gauri Kelkar; Dr. Nivedita S.B. (Tropical Journal of Pathology and Microbiology, 2019)
Background: Breast cancer is the second most common cancer after cervical cancer in Indian. Presently breast conservation therapy (BCT) is the preferred treatment for stage I and II breast cancer. Therefore, the present study was undertaken to identify and study these histopathologic factors and correlate them with local recurrence rate. Method: The pathology records of a tertiary cancer referral hospital were systemically scrutinized for two years and 106 women in the age group of 25-70 years with primary operable invasive breast cancer treated by breast conversation therapy (BCT) were studied in depth. Follow-up ranged for 2 to 3 years. Every patient was followed up every 6 monthly by the onco-surgeon and radiotherapist. Cases in which the pathology slides and / or blocks were not available were excluded. Result: The mean age of all the patients was 43.1 years. (Range: 25-67 years.) Majority of the patients are in the age group of 35-44 years (44.3%). Most of the tumours occurred in the upper outer quadrant (62.3%). IDC forms the main group (93.4%) in the various cases studied. Out of 99 IDC only 89 are pure IDC and 10 are with other components. Majority of the cases belongs to grade-III (63.2%). Maximum tumour size is in the range of 2-5 cm (52.8%). Necrosis was one of the main histological factor observed in the present study (12.3%). Overall 7.5% of our patients developed local recurrence, most of them occurred within the first year. Conclusion: Predictive and prognostic histopathologic factors which increase the risk of recurrence are, Presence of extensive intraductal component, Positive cut margin of resection, Presence of Lymphovascular invasion.